2009
DOI: 10.1016/j.taap.2008.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Lung injury, inflammation and Akt signaling following inhalation of particulate hexavalent chromium

Abstract: Certain particulate hexavalent chromium [Cr(VI)] compounds are human respiratory carcinogens that release genotoxic soluble chromate, and are associated with fibrosis, fibrosarcomas, adenocarcinomas and squamous cell carcinomas of the lung. We postulate that inflammatory processes and mediators may contribute to the etiology of Cr(VI) carcinogenesis, however the immediate (0–24 hours) pathologic injury and immune responses after exposure to particulate chromates have not been adequately investigated. Our aim w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 54 publications
2
36
0
Order By: Relevance
“…The resulting excessive production of ROS may lead to oxidative damage to deoxyribonucleic acid (DNA), lipids, and proteins. It has been reported that Cr(VI) compounds may induce injury to brain [26], heart [27], lungs [28], kidneys [29,30], spleen [31], pancreas [32], gastrointestinal system [33], and other vital organs [34] depending on dose level, schemes of treatment, and route of administration [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting excessive production of ROS may lead to oxidative damage to deoxyribonucleic acid (DNA), lipids, and proteins. It has been reported that Cr(VI) compounds may induce injury to brain [26], heart [27], lungs [28], kidneys [29,30], spleen [31], pancreas [32], gastrointestinal system [33], and other vital organs [34] depending on dose level, schemes of treatment, and route of administration [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Tsapakos et al [56] observed low levels of strand break in rat lung after intraperitoneal injection of sodium dichromate (20 mg/kg b.w.) 1 h after injection; however, no strand breaks remained by 24 or 36 h. Moreover, animals exposed intranasallly [28] or intratracheally [57] to particulate Cr(VI), presented injury, inflammation, and a significant elevation of the mutation frequency in the lung. Chorvatovicova et al [58] injected K 2 Cr 2 O 7 (12 mg/kg b.w.)…”
Section: A B C Dmentioning
confidence: 99%
“…This future work would be of particular importance in the case of environmental studies dealing with the toxicity of Cr(VI), which may concern easily extractible Cr(VI) but also more insoluble phases. 40,41 ' ASSOCIATED CONTENT b S Supporting Information. Figures S1ÀS3.…”
Section: Articlementioning
confidence: 99%
“…Repetitive exposure to Cr(VI) results in persistent inflammation, and such an inflammatory microenvironment can further promote lung carcinogenesis (Beaver et al , 2009a; Beaver et al , 2009b). Cyclooxygenase-2 (COX-2) is a key enzyme in the conversion of arachidonic acid to prostanoids, and its activation is associated with inflammation and carcinogenesis (Hakozaki et al , 2014).…”
Section: Introductionmentioning
confidence: 99%